Love is Historically, Institutionally, and Societally Constructed: Using Intersectionality to Examine Racial Issues of Power and Privilege in Queer Relationships - Tahir, Sarah (Perceptions, 2019)
<span data-sheets-value=""1":2,"2":"Research Question: How does interracial attraction expose power dynamics within both hetersexual and queer relationships in accordance with historical and institutional infringements on civil rights? With my research paper, I aim to unpack the power dynamics, present and historically constructed, within white-person of color relationships, as well as the desires for whiteness, cisheteronormativity, and assimilation inherent in them due to hegemonic, normative systems of superiority and dependency. I will use American court cases to demonstrate institutional infringements on queerness as well as scholarly articles which support my point that whiteness infiltrates every aspect of life including relationships and the dynamics which form them, with a specific focus on visibility. "" data-sheets-userformat=""2":515,"3":"1":0,"4":[null,2,65280],"12":0">How does interracial attraction expose power dynamics within both heterosexual and queer relationships in accordance with historical and institutional infringements on civil rights? With my research paper, I aim to unpack the power dynamics, present and historically constructed, within white-person of color relationships, as well as the desires for whiteness, cisheteronormativity, and assimilation inherent in them due to hegemonic, normative systems of superiority and dependency. I will use American court cases to demonstrate institutional infringements on queerness as well as scholarly articles which support my point that whiteness infiltrates every aspect of life including relationships and the dynamics which form them, with a specific focus on visibility.